Performance of InGaN-GaN LEDs fabricated using glue bonding on 50-mm Si substrate - Peng, WC; Wu, YS (My University, 2006)
Vertical InGaN-GaN light-emitting diodes (LEDs) epitaxial films were successfully fabricated on a 50-mm Si substrate using glue bonding and laser liftoff technology. A high-temperature stable organic film, rather than a solder metal, was used as the bonding agent. It was found that the light output of the vertical InGaN LED chip exceeded that of the conventional sapphire-substrate LEDs by about 20% at an injection current of 20 mA. The vertical InGaN LEDs operated at a much higher injection forward current (280 mA) than sapphire-substrate LEDs (180 mA). The radiation pattern of the vertical InGaN LEDs is more symmetrical than that of the sapphire-substrate LEDs. Furthermore, the vertical InGaN LEDs remain highly reliable after 1000 h of testing.
Keywords: glue bonding; InGaN-GaN; laser liftoff; light-emitting diodes (LEDs)